Reducing Vulnerability to Speculative Attacks - Calvo, Sara (World Bank, Washington, DC, 2012)
The note focuses on the speculative attack on domestic assets, which can occur irrespective of country's fiscal situation, suggesting political economy considerations may be the reason. However, recent events have reopened the debate on how to reduce vulnerability to capital outflows in developing countries, though other risk factors have been identified, which if minimized, can still reduce vulnerability to speculative attacks. It addresses the perils of inconsistent macroeconomic policies, as evidenced in Argentina, where the Central Bank was financing the government's budget deficit by creating money, while trying to keep the exchange rate fixed. Moreover, a speculative attack on bonds, instead of currency, can also lead to a devaluation, such as a sudden shift in perceptions about macroeconomic stability, may lead to a loss in reserves, as in Mexico's 1994 crisis, when high interest rates associated with a currency defense was perceived as intolerable. This is substantiated through case studies, which further include the expectation of realized contingent liabilities, a drop in tax revenues associated with business cycles driven by capital inflows, and investor refusal to roll over debt in countries other than the crisis country, know as contagion. Recommendations include the adoption of consistent macroeconomic policies; reduction of debt rollover risks; strengthening financial regulation; and, capital flows regulation.